Developing a Practice of African-Centred Solidarity in Child and Youth Care - Amponsah, Peter; Stephen, Juanita (International Journal of Child, Youth and Family Studies, 2020)
What does it mean to be an ally? More specifically, what does it mean to do the work of allyship in support of Black young people and families? As educators, researchers, and practitioners in the child and youth care field, we seek to initiate a conversation pertaining to the epistemological make-up of child and youth care practice and the movement towards persistent and intentional solidarity work as a framework for cross-racial engagement. Through a series of critical questions, this paper seeks to deconstruct the taken-for-granted practices of White Eurocentric allyship in favour of a new vision for the future of solidarity work with African-descended children, youth, and their communities.